KATA PENYUKAT DALAM BAHASA MINANGKABAU DI NAGARI SUNGAI GERINGGING KABUPATEN PADANG PARIAMAN - Saputra, Andri; Agustina, Agustina; Juita, Novia (Universitas Negeri Padang, 2018)
This research purposed to describe (1) forms of word â€œPenyukatâ€ Â (2) to clasify the using the wordÂ â€œpenyukatâ€ in Minangkabaunese language at Nagari Sungai Geringging Padang Pariaman district. This research is qualitative research by using descriptive methode. This researchâ€™s subject is the word â€œpenyukatâ€ in Minangkabaunese language at Nagari Sungai Geringging Padang Pariaman district. The data which been taken analyzed by followingÂ steps: (1) transcripted the data from many resources into writing text, which is form recorded data, interview and observation. (2) to clasify the form of word â€œPenyukatâ€ into Minangkabaunese language, (3)Â to analysis which match with the purpose of research (4) to formulating the result of the research. There are two results from this research. First, according the form, the word â€œpenyukatâ€ Â in Minangkabaunese language which used by people at Nagari Sungai Geringging can be divided into two kinds, (a) the word â€œPenyukatâ€ in basic form, (b) the word â€œpenyukat â€œ in complexÂ form.Â The word â€œpenyukatâ€ Â Â in complexÂ form divided in two kinds, the word â€œ penyukat â€œ with afixes and the word â€œpenyukat â€œÂ composition. The wordÂ â€œpeyukatâ€ with afixes consist ofÂ two infix, the afixes which ending with â€“an and afixes by combining ba-/-an. Second, according the clasification of using the word â€œpenyukat â€œ inÂ Minangkabaunese language in Nagari Sungai Geringging Padang Pariaman district was found three forms of using, they are : (1) the word â€œpenyukatâ€ for human, (2) the word â€œ penyukatâ€ Â for animal,(3) the word â€œpenyukatâ€ for noun which classified in general and specifically.Keywords:Â quantifier, minang language, form